Faceted fatty acid vesicles formed from single-tailed perfluorinated surfactants. Issue 36 (28th September 2015) - Zhang, Juan; Xu, Guiying; Song, Aixin; Wang, Lin; Lin, Meiqin; Dong, Zhaoxia; Yang, Zihao
<x xml:space="preserve">Abstract</x> Polyhedral fatty acid vesicles spontaneously formed at a suitable pH value and ratio of perfluorinated fatty acid/soup.